Pung Chhiv Kek [Cambodia, Activist] - Kek, Pung Chhiv (Institutional Knowledge at Singapore Management University, 2015)
Dr Pung Chhiv Kek is the Founder and President of the Cambodian League for the Promotion and Defense of Human Rights (LICADHO) and was nominated in 2005 for the Nobel Peace Prize as part of the 1000 Women for the Nobel Peace Prize project. Apart from her work to improve the rights and lives of Cambodians, she talks to DNA about her efforts to bring Hun Sen and Sihanouk together for talks, which later led to the Peace Accords of 1991.